Ox-drawn plough for desilting - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The use of ox-drawn ploughs and scoops for desilting ponds in rangeland areas is both feasible and inexpensive, reports ILCA* in Addis Ababa. The method should prove directly beneficial to and applicable by pastoral groups. Since 1967, an estimated...